Potato glycoside alkaloids exhibit antifungal activity by regulating the tricarboxylic acid cycle pathway of Fusarium solani - Zhang, Chongqing; Chen, Wei; Wang, Bin; Wang, Yupeng; Li, Nan; Li, Ruiyun; Yan, Yuke; Sun, Yuyan; He, Jing (Frontiers in Microbiology, 2024)
Fusarium solani is a pathogenic fungus that causes significant harm, leading to crop yield reduction, fruit quality reduction, postharvest decay, and other diseases. This study used potato glycoside alkaloids (PGA) as inhibitors to investigate their effects on the mitochondrial structure and tricarboxylic acid (TCA) cycle pathway of F. solani. The results showed that PGA could inhibit the colony growth of F. solani (54.49%), resulting in the disappearance of the mitochondrial membrane and the loss of contents. PGA significantly decreased the activities of aconitase (ACO), isocitrate dehydrogenase (IDH), α-ketoglutarate dehydrogenase (α-KGDH), succinate dehydrogenase (SDH), fumarase (FH), malate dehydrogenase (MDH), succinyl-CoA synthetase (SCS), and increased the activity of citrate synthase (CS) in F. solani. After PGA treatment, the contents of acetyl coenzyme A (CoA), citric acid (CA), malic acid (L-MA), and α-ketoglutaric acid (α-KG) in F. solani were significantly decreased. The contents of isocitric acid (ICA), succinyl coenzyme A (S-CoA), succinic acid (SA), fumaric acid (FA), and oxaloacetic acid (OA) were significantly increased (Fig. 1). Transcriptomic analysis showed that PGA could significantly affect the expression levels of 19 genes related to TCA cycle in F. solani.Transcriptomic analysis showed that PGA could significantly affect the gene expression of F. solani. There were 3014 genes with significantly up-regulated expression and 3327 genes with significantly down-regulated expression. Six differentially expressed genes (DEGs) related to the TCA cycle were screened for real-time fluorescence quantitative PCR (RT-qPCR) verification. RT-qPCR results showed that the expression levels of ACO, IDH, α-KGDH, and MDH-related genes were significantly down-regulated, and the expression levels of SDH and FHrelated genes were significantly up-regulated, which was consistent with the results of transcriptomics. In summary, PGA can achieve antifungal effects by reducing the tricarboxylic acid cycle's flow and regulating key genes' expression levels.